A Central Role of RLIP76 in Regulation of Glycemic Control - Awasthi, Sanjay (American Diabetes Association, 2010)
OBJECTIVE: Pathology associated with oxidative stress frequently results in insulin resistance. Glutathione (GSH) and GSH-linked metabolism is a primary defense against oxidative stress. Electrophilic lipid alkenals, such as 4-hydroxy-t-2-nonenal (4HNE), generated during oxidative stress are metabolized primarily to glutathione electrophile (GS-E) conjugates. Recent studies show that RLIP76 is the primary GS-E conjugate transporter in cells, and a regulator of oxidative-stress response. Because RLIP76(−/−) mice are hypoglycemic, we studied the role of RLIP76 in insulin resistance. RESEARCH DESIGN AND METHODS: Blood glucose, insulin, lipid measurements, and hyperinsulinemic-euglycemic and hyperglycemic clamp experiments were performed in RLIP76(+/+) and RLIP76(−/−) C57B mice, using Institutional Animal Care and Use Committee–approved protocols. Time-resolved three-dimensional confocal fluorescence microscopy was used to study insulin endocytosis. RESULTS: The plasma insulin/glucose ratio was ordered RLIP76(−/−) < RLIP76(+/−) < RLIP76(+/+); administration of purified RLIP76 in proteoliposomes to RLIP76(+/+) animals further increased this ratio. RLIP76 was induced by oxidative or hyperglycemic stress; the concomitant increase in insulin endocytosis was completely abrogated by inhibiting the transport activity of RLIP76. Hydrocortisone could transiently correct hypoglycemia in RLIP76(−/−) animals, despite inhibited activity of key glucocorticoid-regulated hepatic gluconeogenic enzymes, phosphoenolpyruvate carboxykinase, glucose-6-phosphatase, and fructose 1,6-bisphosphatase, in RLIP76(−/−). CONCLUSIONS: The GS-E conjugate transport activity of RLIP76 mediates insulin resistance by enhancing the rate of clathrin-dependent endocytosis of insulin. Because RLIP76 is induced by oxidative stress, it could play a role in insulin resistance seen in pathological conditions characterized by increased oxidative stress.